An Assessment on The Effect of Immigrant Entrepreneurship on Local Economic Development in South Africa: A Literature Analysis - Malatji, Thabiso; Makgamatha, Mpho Gift (Universitas Medan Area, 2024)
Migration is an important phenomenon primarily driven by powerful economies and labor market forces. The movement of people across country borders, especially from less developed to more prosperous countries, has a substantial impact in several dimensions. People worldwide have been migrating across continents for food, shelter, safety, and jobs. Today, people are still on the move for the same reasons, and new reasons are arising: they want to be in countries with economic growth and democracy. Moreover, the most important reason for migration is to make money and send remittances to their home countries. The study seeks to assess the effect of immigrants on local economic growth in South Africa. This qualitative study relied much on online secondary data from different search engines. More money is going out of the country than the money coming into the country. The article intends to contribute to the existing body of knowledge and inform local government so that the businesses owned by immigrants can contribute to regional economic growth. Findings from this study revealed that most self-employed immigrants are not banking their money; they send money home to their own countries, hurting South Africa's economy.